Avaliação in vitro da capacidade de materiais que liberam trimetafosfato de sódio associado ou não ao fluoreto em promover a remineralização - Gaban, Gabriel [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The purpose of this study was to verify in vitro the capacity of materials which release sodium trimetaphosphate (TMP), associated or not with fluoride, in promoting remineralization in artificial caries lesion in enamel. Forty-eight enamel blocks (4x3x3 mm) obtained from bovine incisors were selected through the initial surface hardness test (SH1). Artificial caries lesions were induced on the blocks surface and, then, the post-demineralization surface hardness (SH2) was determined. For each material to be analyzed, 12 specimens were fabricated: without TMP and sodium fluoride; without TMP and with 1.6% sodium fluoride; with 14.1% TMP with or without 1.6% sodium fluoride. These specimens were adjusted to the enamel blocks and submitted to pH cycling to promote the remineralization. After cycling, final surface hardness (SH3) test was conducted on the specimens in order to calculate the percentage of surface hardness recovery (%SHR) and the concentration of fluoride (μg F/mm3) on enamel was determined. The results were statistically analyzed considering as variation factors the materials and the variables: percentage of surface hardness recovery (%SHR) and fluoride concentration (μg F/mm3) on enamel. The %SHR data obtained was considered heterogeneous and, for this reason, were submitted to the Kruskal-Wallis test followed by the multiple comparison test of Student-Newman-Keuls. The μg F/mm3 data obtained after logarithmic transformation and homogeneity verification were submitted to the Variance Analysis (ANOVA) followed by the Bonferroni test. The significance level established was 5%. Control and TMP 14.1% groups presented lower %SHR (p=0.609) and statistically different from groups NaF and TMP 14.1%+F (p<0.001), which were statistically similar (p=0.531). Control and TMP 14.1% groups...

O objetivo deste estudo foi verificar in vitro a capacidade de materiais que liberam trimetafosfato de sódio associado ou não ao fluoreto em promover a remineralização em lesão artificial de cárie em esmalte. Foram selecionados 48 blocos de esmalte de incisivos bovinos (4x3x3 mm), pelo teste de dureza de superfície inicial (DS1). Lesão de cárie artificial foi induzida nos blocos e após determinou-se a dureza de superfície pós-desmineralização (DS2). Foram confeccionados 12 corpos-de-prova de cada material analisado: sem TMP e fluoreto de sódio; sem TMP e com fluoreto de sódio a 1,6%; com 14,1% de TMP com ou sem fluoreto de sódio a 1,6%. A seguir, foram adaptados aos blocos e submetidos às ciclagens de pH para promover a remineralização. Em seguida, foi realizada a dureza de superfície final (DS3) para cálculo da porcentagem de recuperação da dureza de superfície (%DSR) e determinada a concentração de fluoreto (μg F/mm3) presente no esmalte. Os resultados foram analisados estatisticamente considerando como fator de variação: materiais e as variáveis: porcentagem de recuperação de dureza de superfície (%DSR) e concentração de fluoreto (μg F/mm3) presente no esmalte. Os dados obtidos de %DSR apresentaram-se heterogêneos e foram submetidos ao teste de Kruskal-Wallis seguidos pelo teste de múltipla comparação de Student-Newman-Keuls. Os dados obtidos de μg F/mm3 após transformação logarítmica e comprovação de sua homogeneidade, foram submetidos à Análise de Variância (ANOVA) seguida do teste de Bonferroni. O nível de significância estabelecido foi de 5%. Observou-se que os grupos controle e TMP 14,1% apresentaram menores %DSR (p=0,609) e estatisticamente diferentes dos grupos NaF e TMP 14,1%+F (p<0,001), sendo estes semelhantes entre si (p=0,531). Os grupos controle e TMP 14,1% mostraram menores...
Keywords: Materiais dentários; Fluoreto de sódio; Fosfatos; Dental materials